2011
DOI: 10.3390/molecules161210541
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of (1S)-2-Carene and (1S)-3-Carene by Picea abies Suspension Culture

Abstract: Biotransformation of (1S)-2-carene and (1S)-3-carene by Picea abies suspension culture led to the formation of oxygenated products. (1S)-2-Carene was transformed slowly and the final product was identified as (1S)-2-caren-4-one. On the other hand, the transformation of (1S)-3-carene was rapid and finally led to the formation of (1S)-3-caren-5-one and (1S)-2-caren-4-one as equally abundant major products. The time-course of the reaction indicates that some products abundant at the beginning of the reaction (e.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Their findings suggested that the oil has a potential cytotoxic activity against DLA cells, where 50 μg of extract/mL was able to inhibit 89% of the cells. The biotransformation of the monoterpenes 2-carene and 3-carene originates oxygenated terpenes that find application in antifungal and antibacterial mechanisms, playing an essential role in plant defense ( Dvorakova, Valterova, Saman, & Vanek, 2011 ). In fact, oxygenated mono- and sesquiterpenes were found to be the main constituents in different species of Zingiberaceae family ( Mesomo et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Their findings suggested that the oil has a potential cytotoxic activity against DLA cells, where 50 μg of extract/mL was able to inhibit 89% of the cells. The biotransformation of the monoterpenes 2-carene and 3-carene originates oxygenated terpenes that find application in antifungal and antibacterial mechanisms, playing an essential role in plant defense ( Dvorakova, Valterova, Saman, & Vanek, 2011 ). In fact, oxygenated mono- and sesquiterpenes were found to be the main constituents in different species of Zingiberaceae family ( Mesomo et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, for these two chemicals an alternative mechanism involving the formation of a hydroperoxide cannot be ruled out (mechanism not shown). These oxidation reactions producing epoxides (or hydroperoxides) have been previously shown to occur in a variety of oxygenated systems. It is therefore likely that such species will be readily produced in the lung. 1,2-Benzisothiazolin-3-one, 3-amino-5-mercapto-1,2,4-triazole, captafol, and penicillamine all contain sulfur atoms that can undergo covalent binding via disulfide exchange (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…a-Phellandrene-8-ol (peak 28) constituted the major alcohol in autoclaved white pepper to originate from the thermal isomerization and oxidation of isoterpenoline, 39 enriched in raw white pepper. a-Phellandrene-8ol also known as p-mentha-1(7),2-dien-8-ol is an oxygenated monoterpene with potential antimicrobial effect 40 previously reported in pepper essential oil. 4 Likewise, linalool (peak 23) and 3-hexenol (peak 1) were detected at trace levels in black pepper and slightly increase upon autoclaving to reach 1.5 and 1.6%, respectively.…”
Section: Headspace-spme-gc-ms Volatiles Analysis Of Raw and Autoclave...mentioning
confidence: 96%